PENGLIBATAN NON MUSLIM SEBAGAI PEGUAM SYARIE DI MALAYSIA: SATU ANALISIS: The Involvement of Non-Muslims As Syarie Counsel in Malaysia: An Analysis - Meerangani, Khairul Azhar; Marinsah, Syamsul Azizul; Ramli, Rushdi (Jurnal Syariah, 2018)
The issue of the involvement of non-Muslims as Syarie counsel in the Shariah Court has triggered a debate among the public, especially involving Muslim scholars and Shariah and Civil legal practitioners in Malaysia. This is due to the actions of a non-Muslim woman lawyer who has filing an appeal challenging the ban issued by the High Court to stop the practice as a Syarie counsel. This study aims to identify the background of the issue and its evaluation from the Islamic law perspective and the contemporary legislation provisions in Malaysia. This issue has been analyzed with regard to the debate on Muslim scholars regarding the involvement of non-Muslims as Syarie counsels and its evaluation based on the legal context and current reality in Malaysia. The prohibition of the involvement was seen as crucial in preserving the relationship between religion in Malaysia and preventing any controversial disputes arising from the issue.